RF and mm-wave power generation in silicon - Wang, Hua; Sengupta, Kaushik (Elsevier, 2016)
This book presents the challenges and solutions of designing power amplifiers at RF and mm-Wave frequencies in a silicon-based process technology. It covers practical power amplifier design methodologies, energy- and spectrum-efficient power amplifier design examples in the RF frequency for cellular and wireless connectivity applications, and power amplifier and power generation designs for enabling new communication and sensing applications in the mm-Wave and THz frequencies. --